PANDANGAN DUNIA DALAM NASKAH DRAMA HÄRÅªT WA MÄRÅªT KARYA ALÄª ACHMAD BÄKATSÄªR - Hidayat, Rahmat (Jurnal CMES, 2014)
This research discusses the following: (1) How is the text structure of HÄrÅ«t Wa MÄrÅ«t play script by AlÄ« Achmad BÄkatsÄ«r? (2) How is the authorsâ world view which is reflected inÂ HÄrÅ«t Wa MÄrÅ«t play script? The objectives of this research are: (1) To describe the text structure of HÄrÅ«t Wa MÄrÅ«tÂ play script byÂ AlÄ« Achmad BÄkatsÄ«r (2) To describe the authorâs world viewÂ HÄrÅ«t Wa MÄrÅ«t play script by AlÄ« Achmad BÄkatsÄ«r. According to the result of this research, the following conclusion can be drawn: first, from the text structure there are three visions as follows: the vision of God which is represented by the characters with the divinity characteristics such as virtue and fidelity; the vision of world which is represented by the characters with worldliness or secular characteristics with badness tendency; and the vision of human which is represented by the characters with human characteristics who is setting out their desire. Second, the author wants to deliver his ideology which has Islamic reformer by putting the precept of God into his works and combining it in history or politic which is related to the reality. World view obtained after theresearch is social realism.